Historiography of the Architecture of Higher Education Institutions in the beginning of the 17th century - the middle of the 18th century - Imamov Ulug’bek Ismailovich (Zien Journals, 2023)
During the Ashtarkhanid dynasty (1601-1753) of the Bukhara Khanate, which played an important role in the history of the statehood of our country, one of the important tasks was the development of science and the reform of the education system. Despite the constant wars and internal conflicts during the Ashtarkhanid era, education, science, and culture did not stop in the Bukhara Khanate. Especially during the Ashtarkhanid era, many madrasahs functioned as educational centers. During this period, the madrasah was considered a secondary and higher educational institution. Madrasahs were accepted by graduates. Madrasah education lasted 7-12 years, depending on the students' abilities, and was from 10 to 40 years old. They are divided into three groups depending on the level of knowledge: A'la (higher), avsat (middle), adno (lower)
Keywords: Madrasahs; mosques; avsat